2020
DOI: 10.31031/ggs.2020.06.000632
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Immunity in a Setting of Covid-19

Abstract: Only precautionary measures are practical at the moment in controlling the COVID-19 pandemic and one such measure is balancing self-immunity. The recent findings about the durability of COVID-19 antibodies in the infected people has put some concerns about the prospects of long-term immunisation methods. In such circumstances, one way of protecting from COVID-19 is by enhancing one's own immune mechanisms. Unfortunately, there is less discussion about this serous issue. Elderly patients are at a higher risk of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…However, the main associations we found across our successive tests suggest that clozapine might have sustained effects on ANC even in individuals without obvious hematological adverse effects. This is consistent with the rationale for the current practice of continued hematological monitoring of people being prescribed clozapine, and supports that additional measures to lower their risk of infections might indeed be warranted even in long term clozapine users ( Siskind et al, 2020 ), for example ensuring their timely access to the annual influenza vaccine ( Pandarakalam, 2020 ).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, the main associations we found across our successive tests suggest that clozapine might have sustained effects on ANC even in individuals without obvious hematological adverse effects. This is consistent with the rationale for the current practice of continued hematological monitoring of people being prescribed clozapine, and supports that additional measures to lower their risk of infections might indeed be warranted even in long term clozapine users ( Siskind et al, 2020 ), for example ensuring their timely access to the annual influenza vaccine ( Pandarakalam, 2020 ).…”
Section: Discussionsupporting
confidence: 77%
“…It is important to better understand the link between clozapine doses, clozapine metabolism and neutrophil counts for several reasons. First, because it would allow for the evaluation of the effectiveness of interventions aimed at lessening the potential detrimental impacts of clozapine on the immune system, such as those proposed in response to the COVID-19 pandemic ( Pandarakalam, 2020 ; Siskind et al, 2020 ). Additionally, in line with recent research on underrepresented populations ( Legge et al, 2019 ), improved comprehension of the biology behind potential adverse effects could help with the refinement of current dosing and titration protocols, therefore increasing the number of TRS patients who can be safely prescribed the medication and benefit from its therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%
“…It may be too speculative to claim that clozapine might act as a modulating factor against severe outcome of COVID-19, by reducing the ratio neutrophils/lymphocytes at the time of the SARS-Cov-2 infection. However, there is evidence that clozapine has immunosuppressant and pro-inflammatory effects at high doses ( Clark et al, 2018 ) and there are suggestions that clozapine may also work on immunomodulation rather than neuromodulation only ( Pandarakalam, 2020 ; Røge et al, 2012). Notably, fluvoxamine (Lenze al., 2020), chlorpromazine ( Plaze et al, 2020 ), valproic acid ( Singh and Singh, 2020 ; Bhargava et al, 2020) and lithium ( Murru et al, 2020 ) have recently been repurposed as potential immunomodulators in COVID-19 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Clozapine remains significantly underutilized, in part due to frequent blood tests requiring regular absolute neutrophil count (ANC) monitoring ( Nichols et al, 2020 ). Adverse reactions to clozapine include neutropenia (2.7% of patients) which can prefigure an impending life-threatening agranulocytosis, (0.4% of patients) ( Atkin et al, 1996 ; Gee and Taylor , 2020; Pandarakalam, 2020 ). Clozapine treatment is also associated with diabetes, obesity, pulmonary disease ( Gee et al, 2020 ; Dragoi et al, 2020 ) and a reported increased risk of COVID-19 infection ( Govind et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%